2019
DOI: 10.3390/jcm8081103
|View full text |Cite
|
Sign up to set email alerts
|

A Finite Element Analysis to Compare Stress Distribution on Extra-Short Implants with Two Different Internal Connections

Abstract: Background: The goal of this study was to analyze the stress distribution on two types of extra-short dental implants with 5 mm of length: An internal hexagon (IH) and morse taper connection (MT). Methods: The three-dimensional model was composed of trabecular and cortical bone, a crown, an extra-short dental implant and their components. An axial load of 150 N was applied and another inclined 30° with the same magnitude. Results: Stress concentrations on the IH implant are observed in the region of the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Splinting implants also reduces biomechanical risks, such as those deriving from the crown-to-implant ratio, which may be unfavorable in some situations. However, most studies investigating crown-to-implant ratios with short and extra-short implants compared with implants longer than 8 mm have found that this factor has no influence on crestal bone stability or implant survival [19][20][21][42][43][44]. It should also be noted that studies using finite element analysis and clinical investigations of crown-to-implant ratio have reported a higher risk of potential prosthetic complications, such as the loosening of structures and possible fractures due to structural fatigue [45,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Splinting implants also reduces biomechanical risks, such as those deriving from the crown-to-implant ratio, which may be unfavorable in some situations. However, most studies investigating crown-to-implant ratios with short and extra-short implants compared with implants longer than 8 mm have found that this factor has no influence on crestal bone stability or implant survival [19][20][21][42][43][44]. It should also be noted that studies using finite element analysis and clinical investigations of crown-to-implant ratio have reported a higher risk of potential prosthetic complications, such as the loosening of structures and possible fractures due to structural fatigue [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Studies using FEA (finite element analysis) of short implants have observed adequate biomechanical capacity in terms of the resistance to and distribution of forces compared with longer implants. In these studies comparing short implants with standard long implants, the application of forces oblique to the implants resulted in a similar stress concentration at the cervical region, and no changes in bone stress were observed due to an unfavorable crown-to-implant ratio; however, changes were observed in prosthetic component stress derived from the unfavorable crown-to-implant ratio [18][19][20]. Systematic reviews regarding the crown-to-implant ratio in single-tooth, non-splinted implants have not found any differences in complication rates between implants of up to 6 mm and longer implants [21].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the peri-implant bone was also subjected to the Mohr-Coulomb method, which allows the differentiation of the impact of tension and compression stresses to occur in a different way. In evaluating the flow limits of each structure, the values considered were as follows: for the titanium implant, the value of 1130 MPa corresponds to 100% [22] and, for bone tissue, 114 Mpa corresponds to 100% in situations of axial load application, and 50 Mpa corresponds to 100% in the application of angled loads [23].…”
Section: Plos Onementioning
confidence: 99%
“…The results showed that there was no difference between the external hexagon and Morse taper system, regardless the bone level. [29][30][31][32] However, there was higher strain in the cervical and apical regions in the models with bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 The unitary restorations are biomechanically complex, especially when replacing posterior missing elements, since the occlusal forces are higher, 21 which can lead to high stresses in the abutment and in the bone, making the system more susceptible to failure. 29 During the load dissipation, the lateral component of the force can be responsible for the torque moment, which have a destructive effect on the cortical bone and can cause complications in the long-term. 30 Frost (1994) 4 conceptualized that the mechanical stimuli in the bone can induce the predictable bone behavior.…”
Section: Discussionmentioning
confidence: 99%